Wielka Wojna i męskość peryferii [rec. Monika Szczepaniak: Habitus żołnierski w literaturze i kulturze polskiej w kontekście Wielkiej Wojny. Kraków: Towarzystwo Autorów i Wydawców Prac Naukowych Universitas, 2017, ss. 400.] - Pfeifer, Kasper (Śląskie Studia Polonistyczne, 2018)
The article discusses Monika Szczepaniak monograph: Habitus żołnierski w literaturze i kulturze polskiej w kontekście Wielkiej Wojny [Habitus Soldier in Polish Literature and Culture in the Context of the Great War]. Following the changes taking place in the Polish habitus at the beginning of the 20th century, the author analyzes the strategies of creating a hegemonic normative militarized masculinity, which in its Polish variant refers to the heroic Romantic-Sarmatian models. In this context, the author discusses minority narratives, presenting various non-heroic masculinity superseded by dominant discourses.